2019
DOI: 10.22437/pdpd.v8i1.12475
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan fiskal daerah dan pengaruh belanja daerah terhadap pertumbuhan ekonomi Kabupaten Tanjung Jabung Barat

Abstract: The purpose of this study was to determine and analyze 1) the proportion of regional expenditure in Tanjung Jabung Barat Regency; 2) regional fiscal capacity in West Tanjung Jabung Regency; 3) the ratio of regional financial independence of West Tanjung Jabung Regency; 4) the financial performance of the regional government of West Tanjung Jabung Regency and 5) the influence of regional spending on economic growth in the West Tanjung Jabung Regency. The data used in this study are secondary data. The analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
1
Order By: Relevance
“…This means that partially EG has no effect on fiscal capacity in each province in Indonesia. This finding contradicts the findings of Suhendra et al, (2019) andJuma'eh et al, (2020) where fiscal capacity is a source of economic growth. Regional revenue sources will be used to create new economic activities that will encourage increased economic growth Khakim et al, (2011) found that ROI have a positive effect on economic growth, but General Allocation Fund (GAF) and other legitimate ROI have a negative effect on economic growth.…”
Section: Results Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…This means that partially EG has no effect on fiscal capacity in each province in Indonesia. This finding contradicts the findings of Suhendra et al, (2019) andJuma'eh et al, (2020) where fiscal capacity is a source of economic growth. Regional revenue sources will be used to create new economic activities that will encourage increased economic growth Khakim et al, (2011) found that ROI have a positive effect on economic growth, but General Allocation Fund (GAF) and other legitimate ROI have a negative effect on economic growth.…”
Section: Results Discussioncontrasting
confidence: 95%
“…Fiscal capacity shows the ability of the region to finance its own government activities, development, and services to the wider community who have paid taxes and levies as a source of regional income. (Suhendra et al, 2019). Directly, the variables of fiscal capacity and government spending have a large impact on increasing economic growth.…”
Section: Linkage Of Eg To Regional Fiscal Capacitymentioning
confidence: 99%
“…Upon analyzing the contribution of Tanjung Jabung Barat Regency's regional budget (APBD), it becomes evident that the funds are primarily utilized for public interests rather than the apparatus's interests. Consequently, this enables the achievement of development goals focused on improving people's welfare through increased economic growth (Suhendra et al, 2019). According to BPS (2020), Tanjung Jabung Barat Regency is the largest contributing area to the agricultural, forestry, and fisheries sectors in Jambi Province, with a GRDP value of 11.19 trillion or 30.14%.…”
Section: Introductionmentioning
confidence: 99%